2020
DOI: 10.1186/s12864-020-07178-6
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected diversity of CRISPR unveils some evolutionary patterns of repeated sequences in Mycobacterium tuberculosis

Abstract: Background Diversity of the CRISPR locus of Mycobacterium tuberculosis complex has been studied since 1997 for molecular epidemiology purposes. By targeting solely the 43 spacers present in the two first sequenced genomes (H37Rv and BCG), it gave a biased idea of CRISPR diversity and ignored diversity in the neighbouring cas-genes. Results We set up tailored pipelines to explore the diversity of CRISPR-cas locus in Short Reads. We analyzed data fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…We reconstructed the CRISPR-Cas locus of 434 strains representing the diversity of the MTC lineages and showing interesting features ( Fig 2 , sample #3). As explained previously, these results and lessons is the subject of the companion article [ 1 ]. Yet we want here to highlight some of the patterns we observed that may be observed in the CRISPRs of other species.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…We reconstructed the CRISPR-Cas locus of 434 strains representing the diversity of the MTC lineages and showing interesting features ( Fig 2 , sample #3). As explained previously, these results and lessons is the subject of the companion article [ 1 ]. Yet we want here to highlight some of the patterns we observed that may be observed in the CRISPRs of other species.…”
Section: Resultsmentioning
confidence: 74%
“…In contrast, CRISPR-builder TB could retrieve IS 6110 sequences insertion positions as shown on strains for which reliable complete genome sequences were available (for instance H37Ra, L4.9, S3 Table , S2 Text ). On other SRR, CRISPRbuilder-TB retrieved between 0 and 2 copies of IS 6110 in the CRISPR locus, in either orientation ( S7 Table , sheet “IS”, and see also companion article Refrégier et al [ 1 ]). The tendency of Crass tool to miss duplications and/or insertions and the neighbouring spacers was further confirmed when applying it to MTC SRR (for instance, on ERR025424, lineage 4.1.2.1, coverage = 555.97, reads length = 116, 8/38 spacers were detected, moreover with errors in their sequences; ERR751335 from L5, S2 Text ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, lack of any shared spacer sequences may be due to the phylogenetic distance of M. canettii from MTBC members, which are mainly variants of M. tuberculosis species and so phylogenetically more related to each other ( 7 , 21 ). Another possibility could be the inability of M. tuberculosis to incorporate new spacers, unlike M. canettii ( 2 , 24 ).…”
Section: Resultsmentioning
confidence: 99%